ANALISIS PENGARUH KEBIJAKAN DIVIDEN, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Adriani, Ika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This research aims that is. 1) To find out whether dividend policy has a significant positive effect on firm value. 2) To find out whether the capital structure has a significant positive effect on firm value. 3) To find out whether the size of the company has a significant positive effect on the value of the company. The method of analysis in this study, namely by using multiple linear regression analysis. The conclusions in this study are: 1) The results of regression testing for the dividend policy variable on firm value show that it has no effect. (hypothesis rejected). Thus, the dividend policy variable has no effect on the firm value on the Indonesia Stock Exchange. 2) The results of the regression test for the capital structure variable on firm value show that capital structure has no significant effect on the Indonesian Stock Exchange firm value. 3) The results of the regression test for the Firm Size variable to Firm Value show a significant value. So the hypothesis is accepted. Thus the size of the company has a negative and significant effect on the value of the Indonesian Stock Exchange (IDX).